Educate to Look: The Importance of Preparing a Visit to a Museum - Marín Tovar, Cristóbal (Eikón / Imago, 2019)
The way the public consumes culture in the 21st century has changed substantially. That´s why the Art museums are taking steps to compete with other alternative forms of leisure, and attract the public, and the non-public, to live an educational experience that is also enjoyable and pleasant. In art museums, thanks to the digital technology, you can make different virtual tours, participate in multimedia games or contemplate in detail works of art, with an excellent educational result. The idea of educating to look is proposed for users to prepare in advance the visit to the museum, using the digital and virtual tools that museums make available on their website. But due to the general lack of visitor’s knowledge, we propose that they also help their audiences to be able to perform the iconographic and iconological interpretation of the works, to overcome the barrier of ignorance, which leads to the feeling of tiredness and boredom, which part of the public reflects on social networks.